1997
DOI: 10.1098/rspb.1997.0051
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distinctiveness of a village population of house mice: relevance to speciation and chromosomal evolution

Abstract: SUMMARYA population of house mice, Mus musculus domesticus, from the village of Migiondo was found to be genetically distinct from nearby populations in Upper Valtellina (Italian Alps). At the supernatant malic enzyme locus, Mod1, the only alleles found in Migiondo (c and n2) were virtually absent from the other populations in the valley, which were characterized by allele a. The extraordinary genetic distinctiveness of the Migiondo population is apparently the result of genetic drift, perhaps coupled with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
2
26
1
4
Order By: Relevance
“…VOL. 8,2009 COMPLEX GENOME IN DEKKERA BRUXELLENSIS 1745 on May 10, 2018 by guest http://ec.asm.org/ isolate auxotrophic mutants in this yeast (our unpublished observations). However, our Southern analysis showed that all five gene probes hybridized to more than one chromosomal band in a majority of strains (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VOL. 8,2009 COMPLEX GENOME IN DEKKERA BRUXELLENSIS 1745 on May 10, 2018 by guest http://ec.asm.org/ isolate auxotrophic mutants in this yeast (our unpublished observations). However, our Southern analysis showed that all five gene probes hybridized to more than one chromosomal band in a majority of strains (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only rarely do geographically separated populations, for example, Mus musculus (8,32), differ in the number and form of chromosomes. The mutability of the genome enhances the adaptability of the species, but it also decreases the viability of the new variant.…”
mentioning
confidence: 99%
“…Founder events and long-distance dispersal associated with colonization of empty habitat can also occur (Hauffe and Searle 1993). Allozyme data have highlighted the importance of these factors in Valtellina, with almost complete differentiation between one village (Migiondo) and the rest of the valley at the Mod1 locus (Fraguedakis-Tsolis et al 1997).…”
Section: Genetic Differentiation In Valtellina: the Impact Of House Mmentioning
confidence: 99%
“…Such premating isolating mechanisms may involve behavioural divergence in mating-signal systems, which are known to make a major contribution to genetic isolation between species (Butlin & Ritchie 1994). In the house mouse, discriminatory aggressiveness has been observed between chromosomal morphs in Scotland , and a case of reproductive isolation that may involve ethological barriers has been documented between Rb races in Italy (Capanna & Corti 1982;Fraguedakis-Tsolis et al 1997). Unravelling the respective contributions of these di¡erent traits to reproductive isolation between the two chromosomal races in Tunisia requires further genetic, ecological and behavioural studies.…”
Section: (C) Reproductive Isolationmentioning
confidence: 99%